Factors related to disaster preparedness among Palu City BPBD employees - Napirah, Muhammad Ryman; Vidyanto; Ashari, Muh. Rizki; Sulaiman, Miftahul Haerati; Sari, Nur Mila (MEDIA ILMU KESEHATAN, 2025)
Background: Reflecting on the earthquake that struck Palu City, it was revealed that the Palu City BPBD's preparedness was not optimal in disaster management efforts, including pre-disaster, emergency response, and post-disaster stages. Based on the results of a preliminary study conducted by researchers through interviews with Palu City BPBD employees, it was shown that employees were not optimal in disaster emergency response and participating in disaster management training. Objective: The purpose of this study was to analyze the relationship between attitudes, emergency response plans, and disaster mobilization with disaster preparedness among Palu City BPBD employees.Methods: This type of research is quantitative research with an analytical design and uses a cross-sectional approach. The sample in this study was 83 Palu City BPBD employees with total sampling. Data analysis was carried out using univariate and bivariate methods.Results: The results of the study indicate a relationship between attitudes (p-value=0.035), emergency response plans (p-value=0.042), and resource mobilization (p-value=0.046) with disaster preparedness among employees at the Palu City BPBD.Conclusion: It is recommended that the Palu City BPBD strengthening attitudes of employees through regular training and simulations, developing detailed, scenario-based emergency response plans, and ensuring resource mobilization.